Brand Experience Sampling in Developing Brand Identification and Effective Customer Experience to Increase Customer Satisfaction in The Automotive Industry - Deniar, Reza; Kurniawati, K; Masnita, Yolanda (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
In the highly competitive automotive industry, understanding the factors infl uencing customer satisfaction is crucial for long-term success. This study addresses the gap in research by comprehensively examining the combined eff ects of Brand Experience, Brand Identifi cation, and Eff ective Customer Journey on customer satisfaction. Using a structural equation modeling method with a partial least squares approach, data were collected through surveys involving individuals with experiences using specifi c car brands. The analysis reveals that both Brand Experience and Brand Identifi cation positively infl uence customer satisfaction. Additionally, the Eff ective Customer Journey, which encompasses how customers interact with brands throughout the purchasing and usage process, signifi cantly impacts customer satisfaction. These fi ndings highlight the need for marketing strategies that holistically integrate Brand Experience, Brand Identifi cation, and Eff ective Customer Journey to enhance customer satisfaction in the automotive sector. The study provides valuable insights for brand managers and marketing professionals to better understand and manage the critical factors shaping customer satisfaction.